A new species of Astreptolabis in mid-Cretaceous amber from northern Myanmar, with the discovery of the first male of Astreptolabidinae (Dermaptera) - Mao, Yue (Zookeys, 2020)
Abstract. A new species of one of the basal families among extant Dermaptera, Pygidicranidae, is described from mid-Cretaceous amber of Myanmar based on two females and a male. Astreptolabis laevissp. nov., belongs to the extinct subfamily Astreptolabidinae, sharing the diagnostic combination of features typical of this group, such as the well-developed compound eyes, large pronotum, and straight and tubular cerci. The discovery of a male with its genitalia partly exerted permits characterization of traits for the subfamily and provides further information on the uniqueness and affinities of the subfamily. In addition, the extended hind wing allows for a comparison between the folding mechanism between these fossils and their modern counterparts, demonstrating considerable conservatism in hind wing evolution among Dermaptera.